MODEL COOPERATIVE LEARNING ROUND ROBIN BERBASIS WEBSITE RANDOM NAME PICKERS TERHADAP PENINGKATAN MAHARAH KALAM - Firdaus, Salsabila; Azizatiz Zahra; Laila Rahma Aryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Although maharah kalam is an integral component of Arabic instruction, many students still struggle to speak Arabic effectively. This condition is largely due to the limited practice of classroom dialogue and the use of monotonous teaching models, which hinder the optimal development of speaking skills. Based on this situation, the present study aims to classify the effect of applying the Cooperative Learning model of the Round Robin type integrated with the Website Random Name Pickers on improving students’ maharah kalam at grade VIII of MTsS Lubuk Kilangan Padang. The study employed a quantitative design using a quasi-experimental method with a non-equivalent control group design. Data were collected through tests (pre-test and post-test) and analyzed step by step using SPSS version 25, including normality tests (Kolmogorov–Smirnov and Shapiro–Wilk), homogeneity tests, and t-tests. The results showed an increase in the average maharah kalām score of students from 76.32 before treatment to 81.47 after the implementation of the learning model, with a significance value of (2-tailed) = 0.013 < 0.05. These findings indicate that the implementation of the Cooperative Learning Round Robin model based on the Website Random Name Pickers has a significant positive effect on improving students’ maharah kalam at grade VIII of MTsS Lubuk Kilangan Padang.